2019
DOI: 10.1002/aur.2115
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 36‐item and 12‐item self‐report World Health Organization Disability Assessment Schedule II (WHODAS‐II) in individuals with autism spectrum disorder

Abstract: The World Health Organization Disability Assessment Schedule II (WHODAS‐II) is one of the most widely used generic assessments for measuring disability levels in both clinical and nonclinical populations, with sound psychometrics that is also aligned with the International Classification of Functioning framework. However, its psychometric properties have not been explored extensively in individuals with autism spectrum disorder (ASD). This study examined the psychometric properties of the 36‐item and 12‐item S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
(64 reference statements)
1
37
0
Order By: Relevance
“…The Swedish version performed similarly to the original [2], and to and to a Norwegian version evaluated in specialized rehabilitation services in Norway [21], as well as to the Swedish 12-item self-report version [11]. WHODAS 2.0 has been validated in many languages and in different psychiatric populations, for example in people with severe mental disorders in rural Ethiopia [22], in patients with autism spectrum disorders in Australia [23], and in Canadian psychiatric emergency patients [6], and always maintained its' psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…The Swedish version performed similarly to the original [2], and to and to a Norwegian version evaluated in specialized rehabilitation services in Norway [21], as well as to the Swedish 12-item self-report version [11]. WHODAS 2.0 has been validated in many languages and in different psychiatric populations, for example in people with severe mental disorders in rural Ethiopia [22], in patients with autism spectrum disorders in Australia [23], and in Canadian psychiatric emergency patients [6], and always maintained its' psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al confirmed the acceptable reliability of the tool (Cronbach’s α-coefficient of 0.86) and conducted a CFA that indicated a good fit (TLI = 0.96; CFI = 0.95; SRMR = 0.06; RMSEA = 0.06). All individual items exhibited a satisfactory correlation with the WHODAS 2.0 summary score (0.42–0.67 for all 12 items), and the items were statistically significantly correlated with the relevant WHOQOL-BREF subscales, indicating the convergent validity of the 12-item WHODAS [ 7 ]. In Poland, a psychometric analysis of the 12-item WHODAS 2.0 has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it shows concurrent validity when compared with other measures of disability or health status or with clinician ratings. [20][21][22][23] Besides, the Clinical Global Impression Scale was used to assess the severity of illness. Severity is rated on a seven-point scale, and the range of responses varies from 1 to 7 (1 = Normal, 2 = Borderline mentally ill, 3 = Mildly ill, 4 = Moderately ill, 5 = Markedly ill, 6 = Severely ill, 7 = Amongst the most severely ill patients).…”
Section: Methodsmentioning
confidence: 99%